2023
DOI: 10.1101/gad.350462.123
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary conservation of the structure and function of meiotic Rec114−Mei4 and Mer2 complexes

Dima Daccache,
Emma De Jonge,
Pascaline Liloku
et al.

Abstract: Meiosis-specific Rec114−Mei4 and Mer2 complexes are thought to enable Spo11-mediated DNA double-strand break (DSB) formation through a mechanism that involves DNA-dependent condensation. However, the structure, molecular properties, and evolutionary conservation of Rec114−Mei4 and Mer2 are unclear. Here, we present AlphaFold models of Rec114−Mei4 and Mer2 complexes supported by nuclear magnetic resonance (NMR) spectroscopy, small-angle X-ray scattering (SAXS), and mutagenesis. We show that dimers composed of t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 55 publications
1
7
0
Order By: Relevance
“…S7 ). The other mutations tested had little or no effect on the Mei4 interaction, but we note that another recent study demonstrated that alanine substitution of K405 in Rec114 or E16 and D18 of Mei4 reduced the thermal stability of the RM complex without blocking complex formation outright ( Daccache et al 2023 ). Our findings, along with those of Daccache et al (2023) , thus indicate that many of the molecular contacts defined in the AlphaFold2 model are important for RM complex formation.…”
Section: Resultsmentioning
confidence: 64%
“…S7 ). The other mutations tested had little or no effect on the Mei4 interaction, but we note that another recent study demonstrated that alanine substitution of K405 in Rec114 or E16 and D18 of Mei4 reduced the thermal stability of the RM complex without blocking complex formation outright ( Daccache et al 2023 ). Our findings, along with those of Daccache et al (2023) , thus indicate that many of the molecular contacts defined in the AlphaFold2 model are important for RM complex formation.…”
Section: Resultsmentioning
confidence: 64%
“…In this model, the open and compact conformations of TOPOVIBL allowing interaction or not with REC114, might represent an active and inactive state for TOPOVIL, respectively. Accumulation of proteins that create a matrix and a condensate-like environment to favor protein-protein interactions also might favor SPO11 dimerization, as proposed in alternative studies (24, 26, 27)(27). As observed in archaea, the SPO11 dimerization could then induce conformational changes of this catalytic subunit, making it efficient for DSB formation activity (Step 3, Fig.…”
Section: Discussionmentioning
confidence: 89%
“…The DNA topological environment sensed by TOPOVIBL could be one of these parameters. The MEI4/REC114 (1:2) complex also might act as a clamp to hold together the two SPO11 subunits (2426) (28). This clamping activity could be mediated by the C-terminal helix of TOPOVIBL that interacts with REC114 and possibly by TOPOVIBL dynamic conformation revealed by our SAXS data (Step 2, Fig.5).…”
Section: Discussionmentioning
confidence: 99%
“…The recent protein structure prediction revolution, spearheaded by AlphaFold2 [ 145 ] has considerably lowered the barriers to high-resolution structural information necessary for point mutant design. From this, separation-of-function mutants can be used to study the details of meiotic recombination, as has been demonstrated recently [ 63 , 108 , 110 ]. At the time of writing, advanced prediction algorithms like AlphaFold2 do not yet possess the capability to model post-translational modifications, small molecule ligands, or nucleic acids.…”
Section: Discussionmentioning
confidence: 99%